Assessment of Coral Reef Fish Stocks From the Nansha Islands, South China Sea, Using Length-Based Bayesian Biomass Estimation - Zhang, Kui; Zhang, Jun; Shi, Dengfu; Chen, Zuozhi (Frontiers in Marine Science, 2021)
The South China Sea (SCS) is one of the world’s main centers for coral reef diversity, with more than one-third of all reef fish species being found in this area. Some indications of overfishing have appeared in typical coral reefs of the SCS, as fish diversities have declined and the average body lengths of dominant fish species have decreased. However, only few assessments of coral reef fish stocks have been conducted, due to insufficient available data. In this study, we applied a newly developed length-based Bayesian biomass (LBB) estimation method to assess 10 dominant coral reef fish species from three main reefs (Yongshu Reef, Zhubi Reef, and Meiji Reef) of the Nansha Islands, SCS. Simulations indicated the estimated parameters were not sensitive to sample sizes (more than 100) using the LBB method. Our results showed that the relative biomass levels (B/BMSY) of Cephalopholis spiloparaea, Cephalopholis urodeta, Lutjanus gibbus, Gnathodentex aureolineatus, Pentapodus caninus, and Cheilinus fasciatus were between 0.16 and 0.45, suggesting an overfishing status; the relative biomass levels of Epinephelus merra, and Parupeneus crassilabris were 0.98 and 1.1, respectively, indicating that they were fully exploited; and the relative biomass levels of Lutjanus kasmira and Melichthys vidua were 1.3 and 2.5, respectively, indicating the populations were in good conditions. The estimates of Lc/Lc_opt were less than one for seven stocks, suggesting that the stocks were suffering from growth overfishing. Therefore, we emphasize the need to reduce fishing mortality and increase the mesh size of the coral reef fishery in the Nansha Islands, to achieve a sustainable yield and biomass.